Intergeracionalidade das habilidades sociais entre pais e seus filhos adolescentes - Comodo, Camila Negreiros (2012)
The Behavior Analysis assigns an important role in the cultural practices of a group, since they refer to behavior patterns passed down through generations that may favor the development of a healthier culture. At the same time, the literature of social skills theoretical and practical has produced evidence that an elaborate repertoire of social skills is configured as a protective factor to deficits and pathologies, contributing to individuals quality of life. Thus, the learning of social skills, which can occur through the transmission between generations (intergenerational), is essential both for the healthy development of children and teenagers as well as a more ethical culture. Considering this evidence the present study aims to: (1) characterize the repertoire of social skills of parents and teenagers, (2) analyze the characteristics of social skills more frequently in the repertoires of parents and children respondents; (3) identify the possible correlation between the repertoire of social skills of parents and children.To this end, a sample of 142 students aged 12 to 17 years of public and private schools as well as their parents were evaluated in relation to their repertoire of social skills through inventories IHS-Del Prette and IHSA-Del Prette. The data were analyzed descriptively and inferentially by the Kruskal-Wallis H and Spearman tests. The results suggest that the social repertoires of adolescents and parents are differentiated according to gender of respondents, age and parental education. The data also show that there are transmissions of social skills classes (assertiveness, empathy, emotional approach and self-confidence) from parents to children. This transmission is differentiated according to the sex of parents and children and age of children. Therefore, are discussed the importance of an elaborate social skills repertoire in parents, as well the contribution that these results can bring to the culture.